PALU CITY GOVERNMENT POLICY IN INCREASING STUDENTS' RELIGIOUS KNOWLEDGE THROUGH THE PALU KANA MAPANDE PROGRAM - Safrudin, Safrudin; Idhan, Mohamad; Rusdin, Rusdin; Erniati, Erniati (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2023)
This article discusses the evaluation of the implementation of make-a-match type cooperative learning model to improve learning outcomes of Islamic religious education in a senior high school in Central Sulawesi. The research used a qualitative method with data collection techniques such as direct observation, in-depth interviews, and document analysis. The research findings show that Islamic religious education learning by implementing the make-a-match type cooperative learning model at Banawa Senior High School increased students’ achievement results. The make-a-match type cooperative learning model are better than conventional learning because the students show anthusiasm in learning process. The make-a-match type cooperative learning model evaluates each presentation of material to maintain retention (memory), increasing motivational effects and new knowledge, and also increasing memory by adding creations that connect students' new ability to previous knowledge.